Numerical solution of infinite boundary integral equation by using Galerkin method with Laguerre polynomials. - Nik Long, Nik Mohd Asri; Eshkuratov, Zainidin K.; Yaghobifar, Mohammad; Hasan, M. (World Academy of Science, Engineering and Technology (WASET), 2008)
In this paper the exact solution of infinite boundary integral equation (IBIE) of the second kind with degenerate kernel is presented. Moreover Galerkin method with Laguerre polynomial is applied to get the approximate solution of IBIE. Numerical examples are given to show the validity of the method presented.